A Withanolide-rich Fraction of Athenaea velutina Induces Apoptosis and Cell Cycle Arrest in Melanoma B16F10 Cells - Almeida, Alisson A.; Lima, Graziela D. A.; Eiterer, Marinês; Rodrigues, Laís A.; A. do Vale, Juliana A.; Zanatta, Ana C.; Bressan, Gustavo C.; de Oliveira, Leandro L.; Leite, João P. V. (Planta Medica, 2021)
Athenaea velutina is a promising Brazilian shrub with cytotoxic and antimigratory properties against cancer cells. However, the mechanism of induction of cancer cell death and the compounds involved remain unknown. To ascertain these bioactive compounds, bioassay-guided fractionation was performed, alongside the appropriate in vitro tests. A withanolide-rich fraction (FAv_5) from the dichloromethane extract increased cytotoxic activity by 1.5-fold (IC50 = 2.1 µg/mL). Fourteen withanolide steroids were tentatively identified for the first time for this species by mass spectrometry coupled to liquid chromatography (LC MS/MS), including withanolide A, aurelianolide A, and aurelianolide B. FAv_5 significantly decreased cell proliferation, migration, and invasion with a selectivity index greater than 8 for B16F10 cells. Furthermore, flow cytometry with annexin V fluorescein isothiocyanate/propidium iodide (V-FITC/PI) staining showed FAv_5 to promote cell cycle arrest at the G0/G1-phase as well as apoptotic cell death. Overall, these findings highlight A. velutina as a source of withanolide-steroids that inhibit cancer cell proliferation through apoptosis and cell cycle blockade mechanisms. Details on the geographic distribution of A. velutina and species conservation strategies have also been highlighted.
Keywords: Athenaea velutina; Solanaceae; withanolides; apoptosis; cell cycle arrest; geographic distribution